Analysis of Students' Creative Thinking Abilities in Science Learning in Elementary Schools - PUTRI Melianti; Anisya Fitriani; Adinda Wulan Fitriyah (CV. Akademi Merdeka, 2026)
Creative thinking is a skill that student must posses to support the mastery of 21 st-century skills. In natural science (IPA) learning, this ability plays a role in facilitating students to create ideas, innovation, and constructive thinking. This research aims to explore the level of creative thinking ability of fourth-grade students in science learning at the elementary school level. The type of research used is the qualitative descriptive method. The subject of the research were 50 students, consisting of 28 female students and 22 male students. The data collection technique was carried out through observation, test, and documentation. The research instrument consist of eight essay question formulated based out five indicators of creative thinking ability, namely fluency, flexibility, originality, elaboration, and metaphorical thinking. The data analysis technique used was source triangulation. The result of the data analysis show that the aspect of fluency dominates the students achievement, followed by flexibility. Meanwhile, originality, elaboration, and metaphorical thinking fall into the less satisfactory category. These findings indicate that students tend to be able to present original ideas, but still need reinforcement in flexible thinking as well as in the use of analogies or metaphors.